PENERAPAN METODE ACTIVITY BASED COSTING SYSTEM DALAM MENENTUKAN HARGA SEWA KAMAR PADA HOTEL TRANSIT KOTA LUBUKLINGGAU - Ronal Aprianto (Jurnal Media Ekonomi (JURMEK), 2016)
This study aims to determine the price of hotel room rental using the Activity Based Costing System method and to find out the difference in room rental prices using the traditional method (Unit Cost) with the Activity Based Costing System method in Lubuklinggau City Transit Hotels. The data in this study uses primary data, where data is processed by the researcher himself. The method of data analysis researchers used a qualitative method where quantitative analysis is a non-statistical analysis that helps in research. The data obtained either in the form of numbers or in the form of tables that are interpreted properly. In accordance with the data obtained, qualitative analysis is used to explain the relationship between variables that are affected or that affect. In other words, qualitative analysis is carried out for qualitative data collected from exploratory research (interviews, discussions, projection techniques) that is in the form of words or sentences and data collection methods using interviews and documentation. The results of the research on room rental prices using the Activity Based Costing System method produce for the type of rooms that are oversized namely room type suit rooms, superior "tripple", superior rooms, and standard. Whereas for the type of room that is Understanding is the Junior Suit Room and Deluxe Room Type.